Evolution of beach profiles at the German Baltic Sea during and after large-scale beach nourishment: bar formation and sand redistribution - Tiede, Jan; Jordan, Christian; Siewert, Marcus; Sommermeier, Knut; Schlurmann, Torsten (Frontiers in Marine Science, 2024)
Coastal zones, critical for their ecological and economic significance, are increasingly vulnerable to storm surges, sea-level rise, and land subsidence. Traditional defense mechanisms, such as dikes and seawalls, are often costly and environmentally taxing. This research highlights how beach and dune systems, key components of coastal protection in the Baltic Sea region, evolve following sand nourishment. Dunes, sustained by periodic sand replenishments, play a critical role in shielding the coast from storm surges, high water levels, and erosion. High-resolution data from Unmanned Aerial Vehicle surveys, alongside terrestrial field observations, provide insights into the morphological changes post-nourishment, including the formation and dynamics of sandbars. Additionally, we demonstrate how UAV photogrammetry can achieve significantly improved change detection through advanced co-alignment techniques, resulting in enhanced precision and reliability of the data. The study underscores the importance of dunes and sandbars in mitigating erosion and advocates for their continued inclusion in coastal protection strategies. The results emphasize the need for long-term monitoring and adaptive management to optimize nourishment effectiveness, supporting sustainable coastal development and resilience against future challenges.